2022
DOI: 10.3390/dj11010010
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Diseases and Biological Dental Implant Complications: A Narrative Review

Abstract: The relationship between periodontitis and such systemic disorders as diabetes, cardiovascular disease and obesity has been extensively investigated. There is less scientific evidence available, however, regarding the influence of systemic diseases on the risk of late failure of dental implant rehabilitation due to peri-implantitis. The aim of the present study was to review the literature on the role of several common systemic disorders (diabetes, obesity, cardiovascular disease, hypertension and osteoporosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Comprehensive measurements of the width of the attached gingiva, vestibule, and soft tissue thickness were conducted to establish clinical parameters as references for subsequent surgical procedures [ 19 ]. Factors such as oral hygiene conditions and ensuring the absence of systemic conditions that may impact treatment planning are also considered, as they contribute to the overall success of the treatment [ 20 , 21 ].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive measurements of the width of the attached gingiva, vestibule, and soft tissue thickness were conducted to establish clinical parameters as references for subsequent surgical procedures [ 19 ]. Factors such as oral hygiene conditions and ensuring the absence of systemic conditions that may impact treatment planning are also considered, as they contribute to the overall success of the treatment [ 20 , 21 ].…”
Section: Case Reportmentioning
confidence: 99%
“…Comprehensive measurements of the width of the attached gingiva, vestibule, and soft tissue thickness were conducted to establish clinical parameters as references for subsequent surgical procedures [19]. Factors such as oral hygiene conditions and ensuring the absence of systemic conditions that may impact treatment planning are also considered, as they contribute to the overall success of the treatment [20,21]. Based on a thorough assessment of relevant clinical parameters, the proposed treatment plan involves the simultaneous installation of implants in the maxillary anterior teeth, complemented by the addition of xenograft mixed with autogenous bone graft and the strategic utilization of ADM as a barrier to enhance mucosal tissue thickness [22,23].…”
Section: Case Reportmentioning
confidence: 99%
“…Careful evaluation of bone mineral density can improve the prognosis for dental implants in patients with osteoporosis [34]. According to most of the studies that were reviewed by Sbricoli et al, the results showed no difference between patients with metabolic bone disease and healthy patients in the survival rates of dental implants, so there isn't enough evidence to argue that osteoporosis increases peri-implantitis risks [35]. A study by Shibili et al compared the histological properties of implants in patients with and without osteoporosis; neither group had different percentages of bone-implant contact and results weren't different between groups either after osseointegration was achieved.…”
Section: Osteoporosismentioning
confidence: 99%
“…After complete healing, the edentulous space will be replaced by placement of 2 implants in area 3.2 and 4.3 supporting a 5-unit splinted dental fixed dental prosthesis [31].…”
Section: Case Presentationmentioning
confidence: 99%